Organisations Surrounded by Silence: Evaluation of Tourism and Hospitality Literature within Employee Silence, Quiet Quitting, and Quiet Firing - Esra Katırcıoğlu (Journal of Tourismology)
Three distinct workplace phenomena—employee silence, quiet quitting, and quiet firing—have received intense attention recently. While acknowledging their differences, a key similarity among them is the lubricant of silence in the workplace. Silence is a widely recognised phenomenon in the tourism and hospitality industries. This study aimed to evaluate employee silence, quiet quitting, and quiet firing. Accordingly, a systematic literature review was conducted. According to the findings obtained, the number of studies on employee silence increased in 2022 and 2023, within the period when quiet quitting and quiet firing were introduced. However, the number of studies on quiet quitting and quiet firing was limited. Employee silence studies were heavily constructed on a specific theoretical background, especially conservation of resources and social exchange theories, while quiet quitting and quiet firing were highly descriptive and urged for future studies. Most employee silence studies adopted quantitative research methods, whereas studies on quiet quitting and quiet firing were conducted in a qualitative manner, trying to describe the phenomena to form a basis for future studies.